MEMAHAMI ASPEK FILSAFAT DALAM ILMU KOMUNIKASI DAN DAKWAH - Nurhayati Nurhayati (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
Three aspects of philosophy have become the study of academics and practitioners, namely aspects of ontology, epeistemology, and axiology. This paper deals with the determination of the concepts of onilology, epistemology, and axiology in the science of communication and da'wah. The method used is the literature review method by collecting data by reviewing a variety of literature in the form of books, journals, and online sources. The results of this study explain that by understanding the concepts of ontology, epistemology, and axiology, the search for truth and the science of communication and propaganda can be obtained essentially. In the case of Islamic broadcasting communication, the process of presenting information cannot be compared to presenting information in the context of public communication that is more concerned with business and financial interests. In Islamic broadcasting communication, communication must be seen in an Islamic context where the information presented must be true, obtained through the correct method (epistemology), and has a good aesthetic so that it can be justified.